Revolutionizing Digital Advertising: The Role of Blockchain in Marketing Strategies - Lusekelo Kibona (International Journal of Advanced Science and Computer Applications, 2026)
This study explored the role of blockchain technology in revolutionizing digital advertising, focusing on its awareness, adoption, and impact on marketing strategies. With a sample size of 98 participants, the research examined key indicators such as the level of awareness and understanding of blockchain concepts, the extent of adoption in digital advertising, and perceptions of its benefits and challenges. Findings revealed that while awareness and moderate understanding of blockchain were widespread, significant challenges hindered its full integration into advertising infrastructures. Despite these obstacles, the potential of blockchain to enhance transparency, prevent ad fraud, and improve targeting was recognized by many respondents. The study concludes that strategic efforts are needed to overcome adoption barriers and recommends targeted education, collaboration, and gradual implementation to unlock blockchain's full potential in digital advertising.